A contribution to the knowledge of the genus Atractides Koch, 1837 (Acari: Hydrachnidia, Hygrobatidae) in France - Pešić, Vladimir; Smit, Harry; Gerecke, Reinhard (Zootaxa, 2012)
A list is given of the water mite material of the genus Atractides Koch, 1837 (Acari: Hydrachnidia, Hygrobatidae) deposited inthe Muséum national d’Histoire naturelle in Paris. Atractides allgaier Gerecke, 2003 and A. remotus Szalay, 1948 are recordedfor the first time for France. From running waters in central-southern France, Atractides marsus n. sp. and A. angelieri n. sp. are described.